JUAL BELI DALAM PANDANGAN ISLAM - Shobirin, Shobirin (Universitas Islam Negeri Sunan Kudus, 2015)
Selling (business) is the exchange of wealth on the basis of mutual willing and the joint agreement. There are four Perversions, namely; (1) Marriage (ijab qobul) (2) the prescribed is run (subject) (3) ma›kud ‹alaih (object) useful objects according to the view of syara› (4) there is a replacement for exchange of goods. The legality of ijab qobul conditions there are three; (a) Do Not in intersperse with other words between ijab qobul, (b) people - the prescribed is run (seller and buyers ) and (c) do not there separated the meaning the seller and buyers still no interaction about ijab qobul. Conditions of the legality of the seller and buyers there are four; (a) reached puberty understanding. (b) Moslems, this condition specifically for buyers in certain objects objects (c) no objects or items in chairman voterâ (ma›kud alaih) and (d) not wasted (waste), the will of their own and there is no compulsion of the other party. Conditions of the legality of goods sold voterâ there are six; (a) must be holy (b) cannot be not to associate with something (c) cannot be in the limit time (d) its own, (e) can be known (seen), (f) can be known to the quality and the weight. various kinds of selling (business) in Islam, seen from the point of view of the two glass eyes of Islamic law there are two valid and cancel and from the eye of goods there are three (1) selling goods that appear, (2) selling mentioned the pharmacodynamic him in the promise and( 3) selling things that are not there. In Islam in business provide current accounts allow to choose to cancel the marriage of selling (business) called khiar, there are three, namely; (1) khiar, assembly (2) khiar conditions (3) khiar disgrace. The wisdom of selling in Islam; (a) that selling (business) in Islam can be valuable social or helped against each other, will grow berbagain reward, (b) business in Islam is one of the ways to maintain cleanliness and halalnya items eaten for himself and his family, (c) business in Islam is the way to combat laziness, unemployment and extortion to others.